Effect of inorganic anions on the performance of advanced oxidation processes for degradation of organic contaminants - Wang, Jianlong; Wang, Shizong (Chemical engineering journal (Lausanne, Switzerland : 1996), 2021)
[Display omitted] •Effect of inorganic anions (IA) on the performance of AOPs was summarized.•Effect of IA on the formation and transformation of reactive species was discussed.•Effect of IA on the stability of oxidants (H2O2 and persulfate) was evaluated.•Effect of IA on the catalytic activity of catalysts was analyzed.•Inorganic anions have influence on comprehensive performance on AOPs. Inorganic anions, such as chloridion, carbonate, phosphate, sulfate and nitrate are ubiquitous in water, they will react with hydroxyl radical and sulfate radical produced during advanced oxidation processes (AOPs), to form chlorine radical, carbonate radical nitrate radical, phosphate radical and sulfate radical, which have a significant influence on the transformation of organic pollutants. It is generally believed that the quenching effect of inorganic anions on reactive species produced in AOPs was the main reason to influence the performance of AOPs. While this reason cannot explain all the results. In addition, at present most of studies only focused on the effect of inorganic anions on the removal efficiency of targeted organic pollutant by AOPs. For better understanding the effect of inorganic anions on the performance of AOPs, it is crucial to comprehensively evaluate the effect of inorganic anions on AOPs. In this review paper, the effect of inorganic anions (such as chloridion, carbonate, phosphate, sulfate and nitrate) on the performance of AOPs, including the transformation of reactive species, stability of oxidants, catalytic activity of catalysts and degradation products, was systematically summarized and reviewed. Firstly, their effect on the formation and transformation of reactive species was discussed, then the effect on the stability of oxidants (H2O2 and persulfate) and catalysts was introduced. Furthermore, the effect on the catalytic activity of catalysts was analyzed. Finally, the effect on the degradation intermediate products of organic pollutants was summarized. This review will provide an insight into the underlying influence mechanism of inorganic anions on AOPs, which is conducive to comprehensively evaluate the effect of inorganic anions on the performance of AOPs.